Penyakit Utama Tanaman Lada di Kabupaten Bangka Selatan: Penyakit Utama Tanaman Lada di Kabupaten Bangka Selatan - Ropalia Ropalia; Rion Apriyadi; Herry Marta Saputra (Universitas Bangka Belitung, 2022)
White pepper production is not in line with the government's extensification and intensification efforts, these are due to disease infection in the pepper plant that tends to increase. Information about disease progression of black pepper plants in production center areas is rarely updated. This research was conducted to observe and determine incidence and severity disease of the black pepper plantations by using the purposive sampling method. The results of the study found three types of disease that infected on black pepper plantations in the South Bangka Regency, namely yellow disease, stem rot disease, and viral disease. The incidence and severity disease are relatively higher in the Tukak Sadai District than others. The incidences of yellow disease, rot stem disease, and viral disease about 3,33 to 90,48 %; 0 to 43,70 %, and 12,5 to 100 %, respectively. The severity of rot stem disease until 43,11 %; and viral disease about 4,58 to 59,57 %.